Turkey's policy toward Syrian refugees: Domestic repercussions and the need for international support - Souad Ahmadoun (Stiftung Wissenschaft und Politik (SWP), 2014)
Turkey's humanitarian activities toward Syrian refugees are part and parcel of its overall policy in the Syria conflict. Yet, it has become increasingly clear that the Turkish government has overestimated its capacities, and thus failed to deliver sufficient assistance to Syrian refugees on its territory. At the same time the government's handling of the refugee issue has led to stark tensions among Turkey's political and societal forces, as Turkey's border regions contend with increasing security and economic challenges. Germany and its European partners should support Turkey in maintaining and improving services to Syrian refugees in Turkey, and in delivering aid more effectively to internally displaced persons (IDPs) inside Syria. They should also push Turkey to adopt a long-term strategy for dealing with Syrian refugees. (SWP Comments)
Keywords: 320